Work Integrated Learning (WIL): South African Universities Preparing Student Teachers for Today's Poor Schools - Msila, V. (South African Journal of Higher Education, 2025)
Plagued by many challenges, the historically disadvantaged schools in South Africa need special attention from initial teacher education programmes at higher education institutions. Recent scientific reports demonstrate that South African learners in primary schools struggle in reading, writing and numeracy. However, along with these challenges, the introduction of digital tools in schools has put more pressure on teachers in all schools. Several educators have been found unprepared for the modern technologies. This case study focused on Work Integrated Learning (WIL) of student teachers at a Gauteng university and how they could be prepared to teach using technology in poorly resourced schools. Eight participants were final year student teachers who shared their experiences from which the study sought recommendations on how teachers could learn to teach in future schools that faced challenges such as poverty of the families and inadequacy of technological resources. The results show that WIL can be a great success in preparing novice teachers to be able to teach in schools that face a myriad of similar challenges. The major findings reveal that WIL is critical in ensuring that relevant initial teacher education prepares teachers who will be able to close the achievement gaps in in disadvantaged schools. Furthermore, teachers who have undergone an effective WIL focusing on poor schools are likely to empower other teachers who will support learner resilience as they improve learner achievement.